Life’s Simple 7 and its impact on chronic bowel disorders: a study on constipation and diarrhea in the U.S. adult population - Sun, Hongzhi; Qi, Lei; Ming, Yiwei; Wang, Weichen; Hu, Maoneng (Frontiers in Medicine, 2025)
BackgroundChronic gastrointestinal disorders, such as chronic constipation and diarrhea, pose significant public health challenges, affecting quality of life and healthcare costs. Life’s Simple 7 (LS7), established by the American Heart Association, encompasses essential health behaviors that may influence bowel health.MethodsWe utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2010, focusing on adults aged 20 years and older. A total of 12,912 participants were included in the analysis. Bowel health was assessed through self-reported questionnaires, while LS7 was evaluated based on seven components: smoking status, physical activity, dietary quality, BMI, blood pressure, blood glucose, and blood cholesterol. Survey-weighted logistic regression models were employed to assess the associations between LS7 and chronic constipation and diarrhea, adjusting for various demographic and health-related covariates.ResultsOur findings revealed a significant inverse association between LS7 adherence and the prevalence of chronic constipation (OR: 0.914, 95% CI: 0.864–0.966, p = 0.003) and chronic diarrhea (OR: 0.883, 95% CI: 0.856–0.912, p < 0.0001). The protective effect of LS7 was more pronounced among males and individuals with a BMI under 30 kg/m2 for chronic constipation, and among younger adults and those without hypertension for chronic diarrhea. Restricted cubic spline analyses indicated a dose–response relationship, particularly for chronic diarrhea.ConclusionThis study highlights the protective role of LS7 in promoting bowel health and preventing chronic constipation and diarrhea. Tailoring public health interventions based on demographic and health characteristics may enhance the effectiveness of strategies aimed at improving gastrointestinal health outcomes.